Archimandrite Feodor (Bukharev) as a literary critic - Sidorova, Tatyana P. (Journal of the Belarusian State University. Philology, 2026)
The article examines the works of Russian writers N. V. Gogol, F. M. Dostoevsky, I. S. Turgenev, N. G. Chernyshevsky in the assessment of Archimandrite Feodor (Bukharev) on the material of his literary-critical articles. The features of literary criticism of Father Feodor as a spiritual writer (intentions, ideological and genre specificity, tools) as well as an analysis of the problems of works of art from the point of view of theological ideas significant for the Archimandrite in the context of the socio-historical and cultural realities of his time are revealed.
Keywords: Archimandrite Feodor (Bukharev); literary criticism; spiritual writer; idea; problem; genres of criticism; tools